Peran Mediasi Kepuasan Kerja Pada Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Pegawai - Fariz Helmi An Nurullah; Suhana Suhana (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2026)
This study aims to examine and analyze the influence of leadership and organizational culture on job satisfaction and employee performance, as well as the mediating role of job satisfaction in the relationship between leadership and organizational culture on employee performance. This research used a quantitative approach with a population of 221 employees consisting of 149 State Civil Apparatus (ASN) and 72 contract employees within the Regional Secretariat of Pekalongan Regency. The sampling technique used was purposive sampling with a sample of 149 ASN employees. Data were collected through questionnaires and analyzed using path analysis with the assistance of SPSS version 23. The analytical techniques included validity test, reliability test, coefficient of determination test, F test, t test, and Sobel test for mediation analysis. The results showed that leadership and organizational culture had a positive and significant effect on job satisfaction and employee performance. Job satisfaction was unable to mediate the influence of leadership on employee performance, but was able to mediate the influence of organizational culture on employee performance. The findings provide theoretical and practical implications for improving employee performance through leadership, organizational culture, and job satisfaction.